Dıffıcultıes faced by turkısh language department students ın translatıon lesson - İbrahim, Rugaş and Mustafa, Hazim (Humanities Journal of University of Zakho, 2023)
This research focuses on the difficulties of translating written texts between Turkish and Kurdish. It includes the analysis and interpretation of words, phrases and expressions in these texts. In our age, translation is of great importance due to globalization, mixing between nations and the rapid development experienced by different societies, and they can also benefit from each other’s experiences and developments through translation. Therefore, we can say that translation is a bridge between different cultures, because it plays an important role in building a strong relationship between nations. We often see that in some translated subjects, the reader does not fully understand or has difficulty in understanding the message expressed, so here we say that translation is not just about changing symbols from one language to another, the main purpose of translation is to convey ideas and is done on the basis of understanding.